FREQUENCY OF ABDOMINAL OBESITY AND ITS ASSOCIATION WITH DIABETES MELLITUS AMONG PEOPLE OF PESHAWAR - Khan, Attaullah; Faheem, Muhammad; Shah, Syed Tahir; Hadi, Abdul; Ullah, Rafi; Ahmad, Salman; Gul, Adnan Mahmood; Shah, Sayyad Farhat Abbas; Jan, Hikmatullah; Hafizullah, Mohammad (Journal of Ayub Medical College Abbottabad, 2015)
Background: Increased body weight is a major risk factor for the metabolic syndrome which is a cluster of coronary heart disease risk factors, like: hypertension, diabetes mellitus and dyslipidaemia. This study was conducted to determine the frequency of abdominal obesity and diabetes mellitus in the population of Peshawar and association between them. Methods: This was a cross sectional study, performed by the Cardiology Department, Lady Reading Hospital Peshawar, in the population of Peshawar. All participants were interviewed in detail regarding known risk factors for coronary artery disease. Waist circumference (‰¥102 cm in male and ‰¥88 cm in females) was used as the surrogate marker for abdominal obesity in already diagnosed patients of type-2 diabetes mellitus. Results: A total of 2548 individuals were included, 71.1% were male. Mean age was 37.94±12.59 years. Mean waist circumference was 90.25±13.45cm in males and 90.52±12.52cm in females. Diabetes was present in 4.4% of the participants and abdominal obesity in 56.6% .Among the male, abdominal obesity was present in 39.4% and diabetes in 2.9%. Out of 39.4% males with abdominal obesity, 2% were diabetic. Out of 38.6% males with no abdominal obesity, 0.9% was diabetic. Amongst the total 559 (21.1%) female subjects, 17.2% were having abdominal obesity and 1.4% was diabetics. Among 123 (4.8%) females with no abdominal obesity, 0.1% was diabetic. A positive association was established between abdominal obesity and diabetes mellitus with a significant p-valve (<0.05). Conclusion: Abdominal obesity is more common in the local population of Peshawar and associated with type-2 diabetes mellitus.